Multiple case study manajemen nyeri secara farmakologi pada pasien pasca operasi dengan spinal anestesi di ruang pemulihan rumah sakit - Syarifuddin; Martyarini Budi; Danang Tri Yudono (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Postoperative pain is a common problem experienced by patients after surgery and can lead to delayed recovery and an increased risk of complications. Adequate pain management is crucial for enhancing patient comfort and the success of perioperative care. Purpose: To determine the profile of pharmacological pain management in postoperative patients who underwent spinal anesthesia in the recovery room at Dr. Tadjuddin Chalid Central Hospital, Makassar. Method: Qualitative descriptive approach with a multiple case study design. The participants consisted of 4 patients selected through purposive sampling. Data were collected through observation, pain assessment using the Numeric Rating Scale (NRS), and documentation of analgesic administration. Results: Most patients experienced initial pain with a score of ≥7. After pharmacological therapy was administered, pain decreased in all participants. The combination of ketorolac and paracetamol reduced pain from a score of 7 to 3, fentanyl reduced it from 7 to 4, and metamizole reduced it from 7 to 3. Meanwhile, patients receiving epidural analgesia exhibited minimal pain from the outset (0–1). Conclusion: Pharmacological pain management is effective in reducing pain intensity in postoperative patients who underwent spinal anesthesia. Keywords: Pharmacological Pain Management; Postoperative Pain; Recovery Room; Spinal Anesthesia. Pendahuluan: Nyeri pasca operasi merupakan masalah umum yang dialami pasien setelah tindakan pembedahan dan dapat berdampak pada keterlambatan pemulihan serta peningkatan risiko komplikasi. Manajemen nyeri yang adekuat sangat penting untuk meningkatkan kenyamanan dan keberhasilan perawatan perioperatif. Tujuan: Untuk mengetahui gambaran manajemen nyeri secara farmakologi pada pasien pasca operasi dengan spinal anestesi di ruang pemulihan Rumah Sakit Metode: Penelitian deskriptif kualitatif dengan rancangan multiple case study. Partisipan berjumlah 4 pasien yang dipilih secara purposive sampling. Data dikumpulkan melalui observasi, pengkajian nyeri menggunakan Numeric Rating Scale (NRS), serta dokumentasi pemberian analgetik. Hasil: Sebagian besar pasien mengalami nyeri awal dengan skala ≥7. Setelah diberikan terapi farmakologi, terjadi penurunan nyeri pada seluruh partisipan. Kombinasi ketorolac dan paracetamol menurunkan nyeri dari skala 7 menjadi 3, fentanyl menurunkan dari 7 menjadi 4, dan metamizole menurunkan dari 7 menjadi 3. Sementara itu, pasien dengan analgesia epidural menunjukkan nyeri minimal sejak awal (0–1). Simpulan: Manajemen nyeri secara farmakologi efektif dalam menurunkan intensitas nyeri pada pasien pasca operasi dengan spinal anestesi. Kata Kunci: Manajemen Nyeri Farmakologi; Nyeri Pasca Operasi; Recovery Room; Spinal Anestesi.